2017
DOI: 10.4102/jsava.v88i0.1529
|View full text |Cite
|
Sign up to set email alerts
|

Census and vaccination coverage of owned dog populations in four resource-limited rural communities, Mpumalanga province, South Africa

Abstract: Dogs (Canis familiaris) are often free-roaming in sub-Saharan African countries. Rabies virus circulates in many of these populations and presents a public health issue. Mass vaccination of dog populations is the recommended method to decrease the number of dog and human rabies cases. We describe and compare four populations of dogs and their vaccination coverage in four different villages (Hluvukani, Athol, Utah and Dixie) in Bushbuckridge Municipality, Mpumalanga province, South Africa. Cross-sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Our finding was similar or slightly higher than those of others studies; 3.4 dogs/km 2 in a rural area in Zimbabwe and 1 dog/km 2 in two rural areas in Chile (Brooks, 1990;Acosta-Jamett et al, 2010). However, previous studies conducted in Tunisia and other regions over the world reported high densities of dogs in both rural and urban areas (Wandeler et al, 1993;Conan et al, 2017;Kitala et al, 2001, Butler andBingham, 2000). Consequently, in rural areas with high density of the dog population, the risk of developing rabies from a probable rabid animal bite is high because access to the post-exposure prophylaxis was limited in these areas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding was similar or slightly higher than those of others studies; 3.4 dogs/km 2 in a rural area in Zimbabwe and 1 dog/km 2 in two rural areas in Chile (Brooks, 1990;Acosta-Jamett et al, 2010). However, previous studies conducted in Tunisia and other regions over the world reported high densities of dogs in both rural and urban areas (Wandeler et al, 1993;Conan et al, 2017;Kitala et al, 2001, Butler andBingham, 2000). Consequently, in rural areas with high density of the dog population, the risk of developing rabies from a probable rabid animal bite is high because access to the post-exposure prophylaxis was limited in these areas.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding indicated that the female dogs produced 1 litter per year and the average litter size was 5 pups as reported in South Africa (Conan et al, 2017) and Chile (Acosta-Jamett et al, 2010) and higher than what was recorded in Australia 3.3 pups per litter (Hudson et al, 2018). In light of these results, sterilization of females in rural areas is strongly recommended as it allows stabilization of the free-roaming population by reducing the population turnover rate.…”
Section: Discussionsupporting
confidence: 53%
“…Rabies in endangered species is an important consideration that can be prevented through the use of oral vaccinations or dropout darts [ 70 , 71 , 72 ]. Reserves that border domestic areas can also encourage the vaccination of domestic animals for rabies in the area, and this approach was effective in the Serengeti [ 73 , 74 ]. Additionally, interactions between carnivore and herbivore species can contribute to disease transmission in protected areas.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinated dogs accounted for 1.2% of all bites -this is in contrast to a study performed in Mpumalanga which showed a vaccination status of 47% amongst dogs. 29 A study carried out in Jos City, Nigeria, found that 93% of biting dogs were unvaccinated. 24 The WHO advocates for a target of 70% rabies vaccination coverage for stray dogs.…”
Section: Discussionmentioning
confidence: 99%